The geometrical concept in manuscripts of Funan: a preliminary study - Ahmad Tarmizi, Rohani; Abdul Kadir, Mohammad Alinor; Mohd, Zahrin Affandi (Elsevier, 2010)
The geometrical concept is not exclusively developed and introduced by the westerners alone. In Asia, the geometrical concept can be traced as early as the existence of the Hinduism and Buddhism in India, much earlier than the Greek, then spread out to Southeast Asian countries before the beginning of Christianity. In this paper we shall discuss the influence of Buddhism geometry to the Malay world in Southeast Asia region during 4th -6th centuries in the era of Funan kingdom. The evidence of the existing Funan manuscripts are parallel to this analysis.